2001
DOI: 10.1116/11.20020801
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nanophase Tungsten Oxides Thin Films by XPS

Abstract: Nanophasic tungsten oxides thin films have been deposited at 500 °C on quartz and glass substrates starting from W(CO)6 using the metal organic chemical vapor deposition technique (MOCVD). Two series of deposition experiments were carried out to make a comparison between the results obtained employing, as reactant gases, O2 mixed with water vapor and a dry mixture of N2 with 25% H2, respectively. The obtained tungsten oxides were analyzed by x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 10 publications
11
44
0
Order By: Relevance
“…For WO 3 the spectrum is deconvoluted in two peaks with weight ratio 4:3, nearly equal width of 1.7 eV, and binding energies of 36.1 ± 0.1 eV for W 4 f 7/2 and 38.2 ± 0.1 eV for W 4 f 5/2 . The positions and shapes of these peaks agree with W in oxidation state +6, as expected for stoichiometric WO 3 2122. For WO 3− x and H z WO 3− x the W 4 f signal is broadened towards lower energy, reflecting the appearance of a new oxidation state lower than +6.…”
Section: Resultssupporting
confidence: 75%
“…For WO 3 the spectrum is deconvoluted in two peaks with weight ratio 4:3, nearly equal width of 1.7 eV, and binding energies of 36.1 ± 0.1 eV for W 4 f 7/2 and 38.2 ± 0.1 eV for W 4 f 5/2 . The positions and shapes of these peaks agree with W in oxidation state +6, as expected for stoichiometric WO 3 2122. For WO 3− x and H z WO 3− x the W 4 f signal is broadened towards lower energy, reflecting the appearance of a new oxidation state lower than +6.…”
Section: Resultssupporting
confidence: 75%
“…The spectrum exhibits two peaks at 232.3 eV (Mo 3d 3/2 ) and 235.4 eV (Mo 3d 5/2 ), confirming the presence of PMo 12 in the PMo 12 @PPy sample, which is in the Mo VI oxidation state . The core‐level W 4f spectrum shows two peaks at 37.54 eV (W 4f 5/2 ) and 35.4 eV (W 4f 7/2 ) with spin‐orbit splitting of 2.14 eV as shown in Figure d. It is further confirmed that the W atoms in PW 12 in PW 12 @PPy exhibit an oxidation state of W VI …”
Section: Resultssupporting
confidence: 79%
“…[32] The core-level W4fs pectrum shows two peaks at 37.54 eV (W 4f 5/2 )a nd 35.4 eV (W 4f 7/2 )w iths pin-orbit splitting of 2.14 eV as shown in Figure 3d.I ti sf urtherc onfirmed that the W atoms in PW 12 in PW 12 @PPy exhibit an oxidation state of W VI . [33,34] High surface and 1D hollow nanostructures are ideally suited for energy-storage devices.B ET analyses of PMo 12 @PPy and PW 12 @PPy samples were carriedo ut and the results are presented in Figure 4. BET surfacea reas for PPy-Npipes, PMo 12 @PPy,a nd PW 12 @PPy samples were found to be 43.11, 36.47, and 34.14 m 2 g À1 ,r espectively.T his decrease in the BET surfacea reas for PMo 12 @PPy and PW 12 @PPy is attributed to the inclusion of the PMo 12 and PW 12 nanoparticles because of their heavy contribution in the hybrid nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy of W 4f 7/2 and W 4f 5/2 is located at 35.8 ± 0.05 and 37.9 ± 0.05 eV (with a peak ratio of 4:3), respectively. The position and the shape of these peaks are representative of W VI oxidation state . In addition, there are two evident peaks at lower binding energy of W 4f 7/2 = 34.9 eV and W 4f 5/2 = 37.0 eV (with a peak ratio of 4:3) in all the figures except Figure h, which are associated with the reduction state (W V ) ions on the film surface, indicating that these POMs films are reduced by Al to form HPBs films .…”
Section: Resultsmentioning
confidence: 88%